Seed priming effects on germination and first growth of the medicinal plant Achillea millefolium L. - Kanatas, Panagiotis; Dellaportas, Vyronas; Kakabouki, Ioanna; Papastylianou, Panayiota (Journal of Phytology, 2020)
This study evaluated the effects of seed priming on germination and growth of A. millefolium by means of laboratory and greenhouse experiments conducted during 2018 in the Agricultural University of Athens. Treatments were GA3 (400 and 800 ppm), potassium nitrate (2% and 4%), polyethylene-glycol (soaking for 12 and 24h) besides an untreated control. Experiment in Petri dishes revealed that GA3 at 400 ppm, potassium nitrate (at concentration 2 and 4%) and PEG significantly increased germination percentage of A. millefolium, while germination rate was also significantly improved as a result of all seed priming techniques. In addition, due to the soil experiment, seedling emergence was significantly increased by GA3 at 400 ppm, potassium nitrate (at both concentrations) and PEG compared with the untreated seeds. Dry biomass of the young seedlings was significantly enhanced by means of GA3 (at 400 and 800 ppm), KNO3 (4%) and PEG for 24 h, indicating the potential effect of seed priming on first growth as well. The results of the present study revealed the significant positive effects of seed priming on A. millefolium seed germination, seedling emergence and early growth.